2007
DOI: 10.1158/0008-5472.can-06-3041
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine (CX3CL1)– and Interleukin-2–Enriched Neuroblastoma Microenvironment Induces Eradication of Metastases Mediated by T Cells and Natural Killer Cells

Abstract: Fractalkine (FKN) is a unique CX3C chemokine (CX3CL1) known to induce both adhesion and migration of leukocytes mediated by a membrane-bound and a soluble form, respectively. Its function is mediated through CX3C receptor (CX3CR), which is expressed by T H 1 immune cells including T cells and natural killer (NK) cells. FKN was shown to be expressed in >90% of 68 neuroblastoma samples as determined by cDNA microarray analysis. Here, we characterized the effect of FKN in the neuroblastoma microenvironment using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…Previous reports have demonstrated that the antitumor effects elicited by fractalkine gene transfer into subcutaneously implanted murine cancer cell lines depend on NK and T cells (Guo et al 2003, Lavergne et al 2003, Xin et al 2005. Consistent with our data, high endogenous fractalkine expression in neuroblastoma (Zeng et al 2007), colorectal cancer (Ohta et al 2005), and gastric adenocarcinoma (Hyakudomi et al 2008), where it is mainly observed in the plasma membrane and cytoplasm of tumor cells, correlated with a higher density of tumor-infiltrating immune cells. In case of RET oncogene-induced tumors, this activation is dependent on the kind of RET mutation, since fractalkine is not expressed in MEN2B tumors lacking immune infiltrates.…”
Section: Dysregulation Of Host Antitumor Response Mechanisms During Rsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous reports have demonstrated that the antitumor effects elicited by fractalkine gene transfer into subcutaneously implanted murine cancer cell lines depend on NK and T cells (Guo et al 2003, Lavergne et al 2003, Xin et al 2005. Consistent with our data, high endogenous fractalkine expression in neuroblastoma (Zeng et al 2007), colorectal cancer (Ohta et al 2005), and gastric adenocarcinoma (Hyakudomi et al 2008), where it is mainly observed in the plasma membrane and cytoplasm of tumor cells, correlated with a higher density of tumor-infiltrating immune cells. In case of RET oncogene-induced tumors, this activation is dependent on the kind of RET mutation, since fractalkine is not expressed in MEN2B tumors lacking immune infiltrates.…”
Section: Dysregulation Of Host Antitumor Response Mechanisms During Rsupporting
confidence: 90%
“…In support of a potential NK-and/or T-cell-mediated antitumor immune response to RET/FMTC expressing cells, a number of genes that are highly upregulated in RET/FMTC tumors code for apoptosis molecules such as Fas ligand (FasL), perforin 1 (Prf1), and the majority of murine granzymes (Gzma, Gzmb, Gzmc, Gzmd, Gzme, Gzmf, Gzmg, Gzmk, Gzmn). Seven genes encode cytokines, cytokine receptors, or chemokines (IL15, Il2rb, Il2rg, Il12rb1, Il18rap, Icos, Vav3, and Cx3cl1) critically involved in the stimulation of T-and NK-cell proliferation and their recruitment in cancerous tissues (Allavena et al 1997, Kuniyasu et al 2001, Dimberg et al 2007, Zeng et al 2007). Ten upregulated genes in this category code for signaling molecules (e.g.…”
Section: Differential Gene Expression In Tumors Induced By Individualmentioning
confidence: 99%
“…Determination of TH Expression in NB Patients TH expression was detected as described previously (27). Briefly, a cohort of 67 primary NBs profiled with the use of Affymetrix Gene Arrays was reanalyzed for expression of TH.…”
Section: Methodsmentioning
confidence: 99%
“…Then, lysis of NXS2-target cells was determined in a standard 51 Cr-release assay. 36 Lysis was calculated as follows: (sample release -spontaneous release)/ (maximum release-spontaneous release) 3 100 per cent.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…Infiltration of primary tumors (NXS2) by T cells was analyzed using anti-CD8 antibody (53-6.7) and anti-CD4 antibody (RM4-5) (BD Pharmingen, Heidelberg, Germany) as previously described. 36 The average number of infiltrating T cells per lm 2 of tumor tissue was quantified by light microscopy analyzing 20 squares of 0.25 lm 2 at a magnification of 2003.…”
Section: Immunohistochemistrymentioning
confidence: 99%